2016
DOI: 10.1021/acs.jctc.6b00420
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Spectral Simulation Protocols for the Amide I Band of Proteins

Abstract: We present a benchmark study of spectral simulation protocols for the amide I band of proteins. The amide I band is widely used in infrared spectroscopy of proteins due to the large signal intensity, high sensitivity to hydrogen bonding, and secondary structural motifs. This band has, thus, proven valuable in many studies of protein structure-function relationships. We benchmark spectral simulation protocols using two common force fields in combination with several electrostatic mappings and coupling models. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 116 publications
3
56
0
Order By: Relevance
“…This vibrational Hamiltonian mapping was demonstrated to work well in combination with the OPLS-AA force field in a recent benchmark study for proteins. 26 …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…This vibrational Hamiltonian mapping was demonstrated to work well in combination with the OPLS-AA force field in a recent benchmark study for proteins. 26 …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Before PAA treatment, the type I collagen matrix revealed characteristic collagen‐related amide I, II, and III bands at 1,200–1,700 cm −1 . Compared with the baseline collagen spectrum, a minor shift in the amide I peak was observed, probably because of newly formed hydrogen bonds (Figs ). A series of collagen wagging vibration bands was detected at amide II, amide III, and between these amides (Figs ).…”
Section: Resultsmentioning
confidence: 99%
“…Explicit solvent (e.g., water) and hetero‐atoms are thus readily (and have been) included in the calculations. The interplay between the force field used to sample conformational dynamics and models used to construct the exciton Hamiltonian is complex . Previous studies have considered CHARMM22 amongst other force fields.…”
Section: Methodsmentioning
confidence: 99%
“…They found that hydration had a significant effect on the computed IR spectra, contributing to the computed red shift of the Amide I bond of different structural components. Recently, Jansen and coworkers have benchmarked several approaches to computing the Amide I band and 2D IR of proteins from MD simulations . Up to four proteins were studied using several combinations of force fields for the MD simulations, electrostatic mappings and couplings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation